2020
DOI: 10.3329/aajfss.v4i1.53874
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of variety and urea fertilizer and its impact on salt-tolerant Boro rice in the coastal area of Bangladesh

Abstract: Salt-tolerant Boro rice response under the interaction of variety and urea fertilizer was assessed in the southern coastal region of Bangladesh for developing coastal agriculture in Bangladesh. A field experiment was carried out at the research field of Agriculture department, Noakhali Science and Technology University (NSTU), Noakhali-3814 in a Randomized Complete Block Design (RCBD) with two varieties viz. BINA dhan-8, BRRI dhan-67 and three doses of urea viz. 250 kg/ ha., 150 kg/ ha. and 120 kg/ ha. were us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Selamat and Ismail (2009), reported that fifty per cent yield is being lost of the salt-sensitive rice genotypes due to salinity. About 30-50% of net cropped area of Bangladesh remains fallow in Rabi and Kharif-1 season, mainly due to soil and water salinity (Hossen et al, 2020). Therefore, researchers and policy makers must invent ways for the efficient utilization of the salinity prone areas.…”
Section: Introductionmentioning
confidence: 99%
“…Selamat and Ismail (2009), reported that fifty per cent yield is being lost of the salt-sensitive rice genotypes due to salinity. About 30-50% of net cropped area of Bangladesh remains fallow in Rabi and Kharif-1 season, mainly due to soil and water salinity (Hossen et al, 2020). Therefore, researchers and policy makers must invent ways for the efficient utilization of the salinity prone areas.…”
Section: Introductionmentioning
confidence: 99%